Molecular and evolutionary analysis of a gene conserved in most Orthopoxviruses - Douglass, Nicola Jennifer (Division of Medical Microbiology, 2017)
Evidence is presented to show that variola and monkeypox viruses evolved independently from a common ancestor. An open reading frame (ORF), potentially coding for a protein of 341 amino acid residues, was found to be conserved in two strains of variola virus (Harvey and Somalia), but degenerate in the Denmark strain of monkeypox virus. Monkeypox virus had a deletion of 391 bp, two 24bp deletions and a single base pair deletion within the coding region of this single copy ORF. The ORF corresponds to the E5R ORF in the published sequence of the Copenhagen strain of vaccinia virus, and the DNA sequence was determined for an additional strain of vaccinia virus, Dairen. A number of other Orthopoxviruses were found to contain this ORF, strengthening confidence in its presence in an ancestral Orthopoxvirus. The equivalent DNA sequence was determined for a number of monkeypox virus strains from West and Central Africa. The Denmark strain was identical to one from Liberia, indicating that this virus probably originated from West Africa. A third virus from West Africa, Benin, was found to have >99% base similarity and the same pattern of deletions as the other two monkeypox viruses. The Zaire strains were identical to one another and different from the West African strains. Like the West African strains, they contained the two 24bp deletions and single base pair deletion. In place of the large deletion they had three smaller deletions of 5-, 9- and 127-bp as well as a single base pair insertion. They also had additional deletions of land 2-bp and an insertion of 3bp. The West African strains have the potential to code for a truncated gene product of 107 amino acid residues, whereas the Zaire strains have no significant ORF. This clearly shows that monkeypox virus has diverged into two geographically isolated groups (Zaire and West Africa). There was >99% base similarity between the two groups, suggesting that the divergence occurred recently. Phylogenetic analysis, by the neighbour-joining method, was undertaken on the corresponding DNA sequences from variola (2 strains), monkeypox (6 strains), vaccinia (1 strain + 2 published sequences), cowpox (2 strains), taterapox, camel pox and ectromelia viruses. For every species gerbilpox virus was the nearest neighbour, suggesting that taterapox virus may be the species most closely related to the common ancestral Orthopoxvirus. Within the variola and cowpox virus species there was >99% DNA sequence conservation. Between species, camelpox virus was the most closely related species to gerbilpox virus, with variola virus, and, more distantly, vaccinia virus, falling into the same group. Cowpox virus was the most diverged species examined. Ectromelia virus shared a branch with cowpox virus. A comparison was made of the intergenic DNA sequence between this ORF and the adjacent downstream ORF. Variation was found, both within and between species, in the form of insertions and deletions. The interrelationships between the different Orthopoxvirus species more or less parallels that of the E5R-equivalent comparison. Some of the viruses had clusters of direct repeats. A pentameric repeated unit was found in 2, 10 and 17 copies in camelpox, gerbilpox and ectromelia viruses respectively. Raccoon poxvirus had a 7bp unit in 13 adjacent copies. The two cowpox viruses had a more complex arrangement of repeated sequences. It was thought that the ESR ORF may prove to be nonessential for virus replication. This was tested by interruption of the E5R gene in vaccinia virus; this did not affect the ability of the virus to form plaques in cell culture, but appeared to reduce the pathogenicity of the 'virus for rabbits. The deduced amino acid sequences were analysed for conserved and variable regions within the gene, to which no specific function has yet been assigned.